Clinical characteristics of two patients with neuronal intranuclear inclusion disease and literature review - Zhao, Bo; Yang, Miao; Wang, Zhiwei; Yang, Qiqiong; Zhang, Yimo; Qi, Xiaokun; Pan, Shuyi; Yu, Yingxin (Frontiers in Neuroscience, 2022)
Background Neuronal intranuclear inclusion disease (NIID) is a rare chronic progressive neurodegenerative disease, with complex and diverse clinical manifestations and pathological eosinophilic hyaline intranuclear inclusions in the central and peripheral nervous systems and visceral organs. Improvements in diagnostic methods such as skin biopsy and gene testing are helpful in revealing the clinical and genetic characters of NIID. Materials and methods We presented two cases of NIID diagnosed by using NOTCH2NLC gene testing and skin biopsy. Diffusion weighted imaging (DWI) showed high linear intensity in corticomedullary junction. We also reviewed all the published NIID cases with positive NOTCH2NLC GGC repeat expansion and skin biopsy results in PubMed. Results Patient 1 was a 63-year-old male who carried 148 GGC repeats and presented with progressive tremor and limb weakness. Patient 2 was a 62-year-old woman who carried 131 GGC repeats and presented with tremors, memory loss and headaches. The most common clinical manifestation of 63 NIID patients in this study was cognitive impairment, followed by tremors. In our study, almost all the patients were from East Asia, the male to female ratio was 1:1.26, with an age of onset of 54.12 ± 14.12 years, and an age of diagnosis of 60.03 ± 12.21 years. Symmetrical high signal intensity at the corticomedullary junction on DWI were revealed in 80.96% of the patients. For the GGC repeat numbers, the majority of GGC repeats were in the 80–119 intervals, with few GGC repeats above 160. The number of GGC repetitions was significantly higher in patients presented with muscle weakness than in other clinical manifestations. Conclusion NIID is a neurodegenerative disease caused by aberrant polyglycine (polyG) protein aggregation. NIID mostly occurs in the elderly population in East Asia, with cognitive dysfunction as the most common symptom. Staging NIID based on clinical presentation is inappropriate because most patients with NIID have overlapping symptoms. In our study, there was no significant correlation between the number of GGC repeats and different phenotypes except for muscle weakness. Abnormal trinucleotides repeat and PolyG protein aggregation maybe common pathogenic mechanism in neurodegenerative diseases and cerebrovascular diseases, which needs to be confirmed by more studies.